O processo de desterritorialização das escolas no campo em Restinga Sêca - RS - Groff, Altair (2022)
To deterritorialize is to undo, to destroy, to remove what was placed. The closing of schools in Restinga Sêca-RS’ countryside deconstructed a territorialization, schools that were built, people who inhabited the countryside, to then direct them to other territories, almost always urban. However, schools were not reterritorialized in the cities in a satisfactory way. Agribusiness sticks to the concentration of land, carrying out monoculture, then undoing the place, space, schools. That said, we emphasize that this research has, as a general objective, to understand the process of deterritorialization driven by the agribusiness of rural schools in the municipality of Restinga Sêca-RS and it’s interface with the deterritorialization of rural communities; and as specific objectives: To identify the territorialized schools in the municipality of Restinga Sêca since before it’s emancipation and, after this, the municipal administrative acts in which the process of deconstitution of schools begin; To prove that modern agriculture, expanded by agribusiness, has been deterritorializing communities, and in particular, countryside schools, and that resistance is constantly present; Recognize the importance of active schools in the Restinga Sêca countryside and the interfaces in the resistance to the non-closing of schools; e Present the deterritorialization of countryside schools in Restinga Sêca-RS and it’s consequences for schools and communities in the countryside and in the city. For this, we used the Dialectical Historical Materialism method. A field research in which we used instruments such as documentation and archive of the city hall of Restinga Sêca-RS; library collection; maps; Internet; depositions; study trips; and non-directive interviews with the participation of the Municipal Education Department of Restinga Sêca, communities surrounding the deactivated schools, teachers and graduates of these schools. As a result, we highlight that, of the 63 municipal schools established in the Restinga Sêca-RS’ countryside, 56 schools were deterritorialized and, with them, the communities followed the same process. We emphasize that the deterritorialization of schools in the countryside still comes from the 1960s, years in which the rural exodus began to take place, and the closing of schools took place in greater numbers in the 90s. despite being rural schools, rural education was built, the Restinga Sêca’ countryside was populated, but, through the so-called modern agriculture, it got rid of people and schools.